Electrochemical and Electronic Devices

By using vinyl fluoride carbonized compound (FEC) as an electrolyte additive in electrochemical equipment and controlling the content of zinc and the composition of electrolytes, the performance problems of positive electrode materials with high zinc content at high temperatures are solved, and better storage, circulation and safety performance are achieved.

JP2025511044APending Publication Date: 2025-04-15NINGDE AMPEREX TECHNOLOGY LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2024557678
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-31
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing positive electrode materials with high zinc content have challenges in storage, circulation and safety performance at high temperatures, especially oxygen release and phase transition problems.

Method used

Electrolyte containing vinyl fluoride carbonized substance is used, and the molar content of nickel in the positive electrode material and the mass content of vinyl fluoride carbonized substance in the electrolyte are controlled to form a solid electrolyte interface film on the negative electrode surface, improve the interface self-healing ability, and reduce the oxidation and decomposition and dehydrogenation reaction of the positive electrode material.

Benefits of technology

It significantly improves the storage, cycle performance and safety performance of electrochemical equipment at high temperatures, reduces the oxidation and dehydrogenation reaction of positive electrode materials, and extends the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025511044000001_ABST
    Figure 2025511044000001_ABST
Patent Text Reader

Abstract

The present invention provides an electrochemical device and an electronic device. The electrochemical device includes a positive electrode and an electrolyte, the positive electrode includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes lithium nickel oxide, and the electrolyte includes fluoroethylene carbonate, and the mass content of the fluoroethylene carbonate is a% based on the total mass of the electrolyte. The charge cutoff voltage UV of the electrochemical device, the molar content x of nickel in the lithium nickel oxide, and the mass content a% of the fluoroethylene carbonate in the electrolyte satisfy the following relationship: [0010] JPEG2025511044000029.jpg1452
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of energy storage, and in particular to electrochemical devices, especially lithium-ion batteries. [Background technology]

[0002] With the development of technology and the increasing demand for mobile devices, the demand for electrochemical devices (e.g., lithium-ion batteries) increases significantly. Electrochemical devices are widely applied in fields such as electric vehicles, consumer electronics, energy storage devices, etc. In order to seek electrochemical devices with high energy density, high discharge performance and high cycle performance, one of the main research directions in the electrochemical energy storage field is to study and improve the electrode materials and electrolyte materials in electrochemical devices.

[0003] At present, among many mature positive electrode materials in commercial electrochemical devices, nickel-containing positive electrode materials, such as nickel cobalt manganese oxide, lithium-rich manganese system, lithium nickel oxide, lithium nickel manganese oxide and other materials, have high mass energy density, and have gradually become one of the main research directions of high energy density materials. However, in order to further improve the energy density, the constant increase in the nickel content in the nickel-containing positive electrode material will cause serious phase change and oxygen release of the positive electrode material. This will bring serious challenges to high temperature storage performance, cycle performance and safety performance.

[0004] In view of this, how to further improve the high temperature storage performance, cycle performance and safety performance of lithium-ion batteries has become the research focus of various lithium-ion battery manufacturers and related workers. The improvement proposals for nickel-containing positive electrode materials still have several different types of defects. Therefore, it is necessary to continue to research and improve nickel-containing positive electrode active materials in order to improve the battery capacity, cycle performance and rate performance of electrochemical devices. Summary of the Invention

[0005] SUMMARY OF THE DISCLOSURE Embodiments of the present invention solve, at least in part, at least one problem existing in the related art by providing a negative electrode active material having a substrateless adhesive film and an electrochemical device including the same.

[0006] According to one aspect of the present invention, some embodiments of the present invention are electrochemical devices, the electrochemical device including a positive electrode and an electrolyte, the positive electrode including a positive electrode active material layer, the positive electrode active material layer including a positive electrode active material, the positive electrode active material including lithium nickel oxide, the electrolyte including fluoroethylene carbonate, the mass content of the fluoroethylene carbonate being a% based on the total mass of the electrolyte, the charge cutoff voltage UV of the electrochemical device, the molar content x of nickel in the lithium nickel oxide, and the mass content a% of the fluoroethylene carbonate in the electrolyte being

number

[0007] According to some embodiments of the present invention, the molar content x of nickel in the lithium nickel oxide is in the range of 0.3 <x≦1である。

[0008] According to some embodiments of the present invention, the lithium nickel oxide has the general formula LiNi x M1 y M2 z O2 or n[Li2MnO3]·(1-n)[LiNi x M1 y M2 z O2], where M1 and M2 include one or more of Co, Mn, Al, Mg, Ti, and Zr, and 0.3≦x≦1, 0≦y≦0.7, 0≦z≦0.7, and 0≦n<1.

[0009] According to some embodiments of the present invention, the charge cut-off voltage U of the electrochemical device is between 4.2V and 5.5V.

[0010] According to some embodiments of the present invention, the mass content a % of fluoroethylene carbonate in the electrolyte is 0.05% to 5.3%.

[0011] According to some embodiments of the present invention, the electrolyte further comprises a sulfur-oxygen double bond compound.

[0012] According to some embodiments of the present invention, the sulfur-oxygen double bond compound includes one or more of 1,3-propane sultone (PS), 2,4-butane sultone, 1,4-butane sultone, ethylene sulfate (DTD), propene-1,3-sultone (PES), methylenemethane disulfonate (MMDS), vinyl sulfone (DVS), 1,2,6-oxadithiane, 2,2,6,6-tetraoxide (CAS: 4720-58-5), 4-methylethylene sulfate (PCS), 3-sulfolene, dihydro-1,3,2-dioxathiolo[1,3,2]dioxathiol-2,2,5,5-tetraoxide (CAS: 496-45-7), and pentaerythritol bicyclosulfate compounds.

[0013] According to some embodiments of the present invention, based on the total mass of the electrolyte, the mass content of the sulfur-oxygen double bond compound is b%, and the mass content b% of the sulfur-oxygen double bond compound and the mass content a% of the fluoroethylene carbonate are:

number

[0014] According to some embodiments of the present invention, based on the total mass of the electrolyte, the mass content b% of the sulfur-oxygen double bond compound is 0.1% to 5%.

[0015] According to some embodiments of the present invention, the electrolyte further comprises an organic solvent and a lithium salt, the organic solvent comprises a linear carbonate, and the linear carbonate is at least one selected from dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

[0016] According to some embodiments of the present invention, the mass content of the linear carbonate is 70% or less based on the total mass of the organic solvent, and / or the mass content of the linear carbonate is 60% or less based on the total mass of the electrolyte.

[0017] According to some embodiments of the present invention, based on the total mass of the electrolyte, the mass content of the linear carbonate having a molecular molar mass of more than 100 in the linear carbonate is c%, and the mass content c% of the linear carbonate having a molecular molar mass of more than 100 and the mass content a% of fluoroethylene carbonate are:

number

[0018] According to some embodiments of the present invention, the mass content c% of linear carbonates with molecular molar masses greater than 100 is between 20% and 60%, based on the total mass of the electrolyte.

[0019] According to some embodiments of the present invention, the electrolyte further comprises an additive, lithium difluorophosphate.

[0020] According to some embodiments of the present invention, based on the total mass of the electrolyte, the mass content of the additive lithium difluorophosphate is d%, and the mass content d% of the additive lithium difluorophosphate and the molar content x of nickel in the lithium nickel oxide are:

number

[0021] According to some embodiments of the present invention, the mass content d% of the additive lithium difluorophosphate is 0.01% to 1%, based on the total mass of the electrolyte.

[0022] According to some embodiments of the present invention, the electrolyte further comprises a polynitrile compound, the polynitrile compound comprising one or more of a dinitrile compound, a trinitrile compound, and a tetranitrile compound.

[0023] According to some embodiments of the present invention, the dinitrile compounds include one or more of succinonitrile, adiponitrile, 1,2-bis(cyanoethoxy)ethane and 1,4-dicyano-2-butene, the trinitrile compounds include one or more of 1,3,6-hexanetricarbonitrile and 1,2,3-tris(2-cyanoethoxy)propane, and the tetranitrile compounds include one or more of 1,1,3,3-propanetetracarbonitrile, 1,1,2,2-ethanetetracarbonitrile, 4-(2-cyanoethyl)-4-cyanopimelonitrile, and pentane-1,3,3,5-tetracarbonitrile.

[0024] According to some embodiments of the present invention, based on the total mass of the electrolyte, the mass content of the polynitrile compound is 0.1% to 5%.

[0025] According to another aspect of the invention, some embodiments of the invention provide an electronic device including the electrochemical device of any of the above embodiments.

[0026] The present invention adopts nickel-containing positive electrode active material, introduces electrolyte containing fluoroethylene carbonate additive, and controls the nickel content in the positive electrode active material and the fluoroethylene carbonate content in the electrolyte, so that the fluoroethylene carbonate forms a solid electrolyte interfacial film on the surface of the negative electrode, and improves the self-repair of the solid electrolyte interfacial film during the use of the electrochemical device. At the same time, it can reduce the oxidative decomposition and dehydrogenation reaction of the fluoroethylene carbonate at high voltage and high nickel content of the positive electrode active material, and significantly improve the high temperature storage performance, cycle performance and float charging performance at high voltage of the electrochemical device using the nickel-containing positive electrode active material.

[0027] Other aspects and advantages of embodiments of the invention will be set forth in the following description, in part, or will be illustrated by the practice of the embodiments of the invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Examples of the present invention will be described in detail below. The examples of the present invention should not be construed as limiting the present invention.

[0029] As used herein, the following terms have the meanings indicated below, unless otherwise specified.

[0030] As used herein, the terms "approximately", "roughly", "substantially" and "about" are used to describe and explain small variations. When used in conjunction with an instance or situation, the term can refer to instances in which the instance or situation occurs exactly as well as instances in which the instance or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term can refer to a range of variation of the numerical value of ±10% or less, such as ±5% or less, ±4% or less, ±3% or less, ±2% or less, ±1% or less, ±0.5% or less, ±0.1% or less, or ±0.05% or less. For example, two numerical values ​​are considered to be "approximately" the same if the difference between the two numerical values ​​is ±10% or less (e.g., ±5% or less, ±4% or less, ±3% or less, ±2% or less, ±1% or less, ±0.5% or less, ±0.1% or less, or ±0.05% or less) of the average value of the numerical values.

[0031] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "one or more of," "one or more of," or other similar terms, means any combination of the listed items. For example, if item A and item B are listed, the short phrase "one or more of A and B" means A only, B only, or A and B. In another example, if item A, item B, and item C are listed, "one or more of A, B, and C" means A only, B only, C only, A and B (excluding C), A and C (excluding B), B and C (excluding A), or all of A, B, and C. Item A can include a single element or multiple elements. Item B can include a single element or multiple elements. Item C can include a single element or multiple elements.

[0032] Additionally, for ease of description, terms such as "first," "second," "third," etc. may be used herein to distinguish between different modules in a figure or set of figures. The terms "first," "second," "third," etc. are not intended to describe corresponding modules unless otherwise specified or limited.

[0033] In the field of electrochemical energy storage, in order to pursue optimal energy density, attempts have been made to use nickel-containing positive electrode active materials with high energy density instead of traditional positive electrode active materials. Nickel-containing positive electrode active materials include, but are not limited to, materials such as lithium nickel cobalt manganese oxide, lithium rich manganese system, lithium nickel oxide, and lithium nickel manganese oxide. Nickel materials have high energy density and operating potential, and nickel resources are abundant, so nickel-containing materials have a great cost advantage compared to materials with high cobalt content. This makes nickel-containing positive electrode active materials a positive electrode active material with great development potential. However, when applying such nickel-containing positive electrode active materials with high energy density, positive electrode active materials with high nickel content are prone to serious phase changes and release oxygen under high voltage environments. This has a serious impact on the high temperature storage performance, cycle performance and safety performance of electrochemical devices.

[0034] In order to improve the above problems, improving the high-temperature storage performance and cycle performance by electrolyte is one of the most economical and reliable methods, and has been adopted by many researchers and developers. Fluoroethylene carbonate (FEC) additives can form a sufficiently stable and low-resistance solid electrolyte interface (SEI) film on the negative electrode, which can significantly improve the cycle performance of the battery and the thickness expansion and gas generation during the cycle process. However, since fluoroethylene carbonate has a relatively high highest occupied molecular orbital (HOMO) energy level, when operating at high voltage, the positive electrode active material with a high nickel content and too much fluoroethylene carbonate are prone to further oxidation and gas generation, which causes the gas to break through the electrochemical device packaged in a soft pack. At the same time, when operating at high voltage, the higher the nickel content in the positive electrode active material, the more vigorous the defluorination and dehydrogenation reaction of fluoroethylene carbonate becomes, which leads to the destruction of the SEI film and the elution of transition metals, significantly deteriorating the high-temperature storage performance, float charging performance, cycle performance, intermittent cycle performance and safety performance of the electrochemical device at high voltage.

[0035] In view of the above problems, according to one aspect of the present invention, some embodiments of the present invention provide an electrochemical device, the electrochemical device includes a positive electrode, an electrolyte and a negative electrode, the positive electrode includes a positive electrode active material layer, the positive electrode active material layer includes a positive electrode active material, the positive electrode active material includes a nickel-containing positive electrode active material, and the electrolyte includes fluoroethylene carbonate (FEC). The present invention can effectively improve the high temperature storage performance, float charge performance, cycle performance, intermittent cycle performance and safety performance of the electrochemical device by controlling the nickel element content in the positive electrode active material layer, the fluoroethylene carbonate content in the electrolyte and the maximum charge cut-off voltage. In some embodiments, when the nickel molar content of the nickel-containing positive electrode active material is x and the fluoroethylene carbonate mass content based on the total mass of the electrolyte is a%, the charge cut-off voltage UV of the electrochemical device of the present invention, the nickel molar content x in the lithium nickel oxide and the fluoroethylene carbonate mass content a% in the electrolyte are:

number

[0036] In some embodiments, the charge cutoff voltage U of the electrochemical device is between 4.2V and 5.5V.

[0037] positive electrode The positive electrode includes a positive electrode current collector and a positive electrode active material layer. The positive electrode current collector may be, but is not limited to, an aluminum foil or a nickel foil, and other positive electrode current collectors commonly used in the art may be used. In some embodiments, the positive electrode active material is a nickel-containing positive electrode active material.

[0038] In some embodiments, the nickel-containing active positive electrode material includes lithium nickel oxide.

[0039] In some embodiments, the lithium nickel oxide has the general formula LiNi x M1 y M2 zO2 or n[Li2MnO3]·(1-n)[LiNi x M1 y M2 z O2], where M1 and M2 include one or more of Co, Mn, Al, Mg, Ti, and Zr, and 0.3 ≦ x ≦ 1, 0 ≦ y ≦ 0.7, 0 ≦ z ≦ 0.7, 0 ≦ n < 1.

[0040] In some embodiments, the range of x in the lithium nickel oxide is 0.3 < x ≦ 1. In some embodiments, the range of x is 0.5 ≦ x ≦ 0.8. In some embodiments, x is 0.33, 0.5, 0.6, 0.8, 0.9, or a range consisting of any two of the above values.

[0041] In some embodiments, the lithium nickel oxide is LiNi x Co y Mn z O2, LiNiO2, LiNi x Mn y O2, and one or more of n[Li2MnO3]·(1-n)[LiNi x M1 y M2 z O2].

[0042] In some embodiments, the positive electrode active material may have a coating layer on the surface or may be mixed with other compounds to have a coating layer. In some embodiments, the coating layer may include at least one coating element compound selected from oxides of the coating element, hydroxides of the coating element, oxyhydroxides of the coating element, oxycarbonates of the coating element, and hydroxycarbonates of the coating element. In some embodiments, the compounds used in the coating layer may be amorphous or crystalline. In some embodiments, the coating elements included in the coating layer may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or mixtures thereof. It should be understood by those skilled in the art that the coating layer may be applied by any method without departing from the spirit of the present invention as long as it does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method known to those skilled in the art, such as spraying, dipping, etc.

[0043] In some embodiments, the positive electrode active material layer may further include a binder. Those skilled in the art should understand that the binder may be any suitable binder material in the art without departing from the spirit of the present invention. In some embodiments, the binder may include, but is not limited to, one or more of polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethyleneoxy-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluorovinyl, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylated styrene butadiene rubber, epoxy resin, and nylon.

[0044] In some embodiments, the positive electrode active material layer may further include a conductive agent. Those skilled in the art should understand that the conductive agent may be any suitable conductive agent material in the art without departing from the spirit of the present invention. In some embodiments, the conductive agent may include, but is not limited to, one or more of carbon-based materials (e.g., one or more of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber), metal materials (e.g., metal powders, metal fibers, and the like, including, for example, one or more of elemental copper, elemental aluminum, and elemental silver), and conductive polymers (e.g., polyphenylene derivatives).

[0045] electrolyte The electrolyte further includes an organic solvent and a lithium salt. The specific types of the lithium salt and the organic solvent are not limited as long as they are within the scope of the present invention. In some embodiments, the organic solvent may include one or more of a chain carbonate, a cyclic carbonate, a chain carboxylic acid ester, a cyclic carboxylic acid ester, and an ether. Examples of organic solvents include, but are not limited to, one or more of dimethyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, methyl butyl carbonate, diethyl carbonate, dipropyl carbonate, dibutyl carbonate, ethylene carbonate, propylene carbonate, butylene carbonate, methyl acetate, ethyl acetate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, butyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl valerate, ethyl valerate, methyl pivalate, ethyl pivalate, butyl pivalate, γ-butyrolactone, and γ-valerolactone. In some embodiments, the lithium salt may be one or more selected from inorganic lithium salts and organic lithium salts. In some embodiments, examples of lithium salts include, but are not limited to, one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate, lithium perchlorate, lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium bis(oxalatoborate) (LiBOB), and lithium difluorooxalatoborate (LiODFB). In some embodiments, the lithium salt is lithium hexafluorophosphate (LiPF6).

[0046] In some embodiments, additives used in the electrolyte of the present invention include, but are not limited to, sulfur-oxygen double bond compounds, lithium difluorophosphate, and polynitrile compounds.

[0047] In some embodiments, the electrolyte further comprises a sulfur-oxygen double bond compound. By adding the sulfur-oxygen double bond compound to the electrolyte, a stable SEI film can be formed on the surface of the positive electrode, and the phase change of the nickel-containing positive electrode active material can be suppressed optimally, and the structural stability of the positive electrode can be enhanced. This can suppress the collapse of the positive electrode active material layer structure at high voltage, and suppress the side effects caused by the collapse with the electrolyte, so that the electrochemical device can exhibit better electrical performance and safety performance. In some embodiments, the sulfur-oxygen double bond compound comprises one or more of 1,3-propane sultone (PS), 2,4-butane sultone, 1,4-butane sultone, ethylene sulfate (DTD), propene-1,3-sultone (PES), methylenemethane disulfonate (MMDS), vinyl sulfone (DVS), 1,2,6-oxadithiane, 2,2,6,6-tetraoxide (CAS: 4720-58-5), 4-methylethylene sulfate (PCS), 3-sulfolene, dihydro-1,3,2-dioxathiolo[1,3,2]dioxathiol-2,2,5,5-tetraoxide (CAS: 496-45-7), and pentaerythritol bicyclosulfate compounds.

[0048] In some embodiments, the mass content a% of fluoroethylene carbonate in the electrolyte is 0.05% to 5.3%, based on the total mass of the electrolyte, and can be, for example, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 5, or a range consisting of any two of the above values.

[0049] In some embodiments, based on the total mass of the electrolyte, the total mass content of the sulfur-oxygen double bond compounds is b%, and the ratio of the total mass content of the sulfur-oxygen double bond compounds b% to the mass content of fluoroethylene carbonate a% is:

number

number

[0050] In some embodiments, the total mass content b% of the sulfur-oxygen double bond compounds is 0.1% to 5% based on the total mass of the electrolyte. In some embodiments, the total mass content b% of the sulfur-oxygen double bond compounds is 0.5% to 3%. In some embodiments, b% can be 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, or a range consisting of any two of the above values.

[0051] In some embodiments, the organic solvent in the electrolyte is a linear carbonate, where the linear carbonate is at least one selected from dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate. In some embodiments, the organic solvent is at least one selected from diethyl carbonate and ethyl methyl carbonate, but does not include dimethyl carbonate. By removing linear carbonates with lower molecular weights, such as dimethyl carbonate, from the electrolyte, the side reaction between the nickel-containing positive electrode active material and the organic solvent in the electrolyte can be reduced, and the consumption of the electrolyte and the resistance of the interface can be reduced.

[0052] In some embodiments, the content of the linear carbonate is 70% or less, based on the total weight of the organic solvent.In some embodiments, the content of the linear carbonate is 60% or less, based on the total weight of the electrolyte.

[0053] In some embodiments, the mass content of the linear carbonate having a molecular molar mass of more than 100, such as, but not limited to, diethyl carbonate or ethyl methyl carbonate, is c%, based on the total mass of the electrolyte solution. The mass content c% of the linear carbonate having a molecular molar mass of more than 100 and the mass content a% of fluoroethylene carbonate are:

number

number

[0054] In some embodiments, the mass content c% of linear carbonates having a molecular molar mass greater than 100 is 20% to 60% based on the total mass of the electrolyte. In some embodiments, c% can be 20%, 30%, 40%, 50%, 60%, or a range consisting of any two of the above values.

[0055] In some embodiments, the electrolyte further comprises lithium difluorophosphate as an additive to enhance protection for the interface between the positive electrode active material layer and the negative electrode active material layer and optimize the electrical performance of the electrochemical device. In some embodiments, based on the total mass of the electrolyte, the mass content of the additive lithium difluorophosphate is d%, and the mass content d% of the additive lithium difluorophosphate and the molar content x of nickel in the lithium nickel oxide are:

number

[0056] In some embodiments, the mass content d% of the additive lithium difluorophosphate is 0.01% to 1% based on the total mass of the electrolyte solution, and in some embodiments, d% can be 0.01%, 0.1%, 0.3%, 0.5%, 1.0%, or a range consisting of any two of the above values.

[0057] In some embodiments, the electrolyte further comprises a polynitrile compound, the polynitrile compound comprising one or more of a dinitrile compound, a trinitrile compound, and a tetranitrile compound.

[0058] In some embodiments, the dinitrile compounds include one or more of succinonitrile, adiponitrile, 1,2-bis(cyanoethoxy)ethane, and 1,4-dicyano-2-butene; the trinitrile compounds include one or more of 1,3,6-hexanetricarbonitrile, and 1,2,3-tris(2-cyanoethoxy)propane; and the tetranitrile compounds include one or more of 1,1,3,3-propanetetracarbonitrile, 1,1,2,2-ethanetetracarbonitrile, 4-(2-cyanoethyl)-4-cyanopimelonitrile, and pentane-1,3,3,5-tetracarbonitrile.

[0059] In some embodiments, the mass content of the polynitrile compound is 0.1% to 5%, based on the total mass of the electrolyte solution.

[0060] negative electrode The negative electrode includes a current collector and a negative electrode active material layer provided on the current collector. The specific type of the negative electrode active material is not particularly limited and can be selected as necessary.

[0061] In some embodiments, the negative electrode active material is natural graphite, artificial graphite, mesocarbon microbeads (abbreviated as MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, lithiated TiO2-Li4Ti5O with spinel structure. 12 and Li-Al alloy.

[0062] Non-limiting examples of carbon materials include crystalline carbon, amorphous carbon, and mixtures thereof. Crystalline carbon can be amorphous or plate-like, flake-like, spherical or fibrous natural or synthetic graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.

[0063] In some embodiments, the negative electrode active material layer may include a binder and may optionally further include a conductive material.

[0064] The binder plays a role of improving the binding between the negative electrode active material particles and the binding between the negative electrode active material and the current collector. Non-limiting examples of the binder include polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic acid (ester)-modified styrene butadiene rubber, epoxy resin, nylon, etc., but are not limited thereto.

[0065] The negative electrode active material layer includes a conductive material to provide electrical conductivity to the electrode. The conductive material can include any conductive material as long as it does not cause a chemical change. Non-limiting examples of the conductive material include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powders such as copper, nickel, aluminum, and silver, metal fibers, etc.), conductive polymers (e.g., polyphenylene derivatives), and mixtures thereof.

[0066] The current collector used in the negative electrode of the present invention may be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0067] Separator A separator may be provided between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the embodiments of the present invention are not particularly limited and may be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic material that is stable against the electrolyte of the present invention.

[0068] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer is a nonwoven fabric, a film, or a composite film having a porous structure. The material of the substrate layer is at least one selected from polyethylene, polypropylene, polyethylene terephthalate, and polyimide. Specifically, the material of the substrate layer may be a polypropylene porous film, a polyethylene porous film, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyvinyl-polypropylene porous composite film.

[0069] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a layer formed by mixing a polymer and an inorganic material.

[0070] The inorganic layer includes inorganic particles and a binder. The inorganic particles are one or more selected from aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. The binder is one or more selected from polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene.

[0071] The polymer layer includes a polymer, and the polymer material is at least one selected from the group consisting of polyamide, polyacrylonitrile, acrylic acid ester polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0072] Without departing from the spirit of the present invention, the structure of the electrode module in the electrochemical device of the present invention can be any suitable electrode module in the art, and is not limited thereto. In some embodiments, the electrode module is a wound structure. In some embodiments, the electrode module can be a stacked structure or a multi-tab structure. In some embodiments, the electrochemical device is a lithium ion battery.

[0073] It should be understood that the preparation method of the positive electrode, separator, negative electrode and electrolyte in the embodiment of the present invention can be selected according to specific needs according to any suitable conventional method in the field without departing from the spirit of the present invention, and is not limited thereto. In one embodiment of the method for preparing an electrochemical device, the preparation method of a lithium ion battery includes winding, folding or stacking the negative electrode, separator and positive electrode in the embodiment in order to form an electrode module, then putting the electrode module into a housing, for example, an aluminum plastic film, injecting an electrolyte, and then carrying out subsequent processes such as vacuum sealing, standing, chemical formation, and shaping on the lithium ion battery put into the electrode module to obtain a lithium ion battery.

[0074] According to another aspect of the invention, some embodiments of the invention further provide an electronic device including an electrochemical device according to an embodiment of the invention.

[0075] The electronic device of the embodiment of the present invention is not particularly limited and can be used in any electronic device known in the prior art. In some embodiments, the electronic device includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, LCD televisions, portable cleaners, portable CD players, mini discs, walkie-talkies, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, bicycle auxiliaries, bicycles, lighting equipment, toys, game consoles, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.

[0076] The following takes lithium ion battery as an example and describes the preparation of lithium ion battery with reference to specific examples.Those skilled in the art should understand that the preparation methods described in the present invention are merely exemplary, and any other suitable preparation methods are within the scope of the present invention. Specific Examples

[0077] In the following, performance evaluation will be carried out for examples of the lithium ion battery of the present invention and comparative examples.

[0078] 1. Preparation of lithium-ion batteries (1) Preparation of positive electrode The positive electrode active material, the conductive agent Super P, and the binder polyvinylidene fluoride were mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) was added, and the mixture was stirred under the action of a vacuum stirrer until the system became uniform and transparent, to obtain a positive electrode slurry. Here, the solid content of the positive electrode slurry was 72 wt%. The positive electrode slurry was uniformly applied onto an aluminum foil as a positive electrode current collector. The aluminum foil was dried at 85°C to form a positive electrode active material layer, and then cold-rolled, cut, and slit, and then dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode piece. The specific type of positive electrode active material used in the positive electrode and the nickel content are described in detail in the examples.

[0079] (2) Preparation of negative electrode The negative electrode active material, artificial graphite, the conductive agent, Super P, the thickener, sodium carboxymethylcellulose (CMC), and the binder, styrene butadiene rubber (SBR), were mixed in a weight ratio of 96.4:1.5:0.5:1.6, deionized water was added, and the negative electrode slurry was obtained under the action of a vacuum stirrer. Here, the solid content of the negative electrode slurry was 54 wt%. The negative electrode slurry was uniformly coated on the copper foil, which was the negative electrode current collector. The copper foil was dried at 85°C, then cold rolled, cut, and slit, and then dried under vacuum conditions at 120°C for 12 hours to obtain negative electrode pieces.

[0080] (3) Preparation of electrolyte In a glove box with a dry argon gas atmosphere, the organic solvent was mixed, then the additive was added, dissolved and thoroughly stirred, and then the lithium salt LiPF6 was added and mixed uniformly to obtain an electrolyte. The concentration of LiPF6 was 1 mol / L. The specific types and contents of the organic solvent and additives used in the electrolyte are described in detail in the Examples. The content of the additive is a mass percentage calculated based on the total mass of the electrolyte.

[0081] (4) Preparation of separator A polyethylene (PE) separator with a thickness of 7 μm was selected.

[0082] (5) Preparation of lithium-ion batteries The positive electrode pieces, separator, and negative electrode pieces were stacked in this order, and a separator was placed between the positive and negative electrodes to serve as an insulator, and then rolled up to obtain a bare cell. After welding the tabs, the bare cell was placed in an aluminum plastic film exterior foil, and the electrolyte prepared above was poured into the dried bare cell, which was then vacuum sealed, left to stand, formed (charged to 3.3 V at a constant current of 0.02 C, then charged to 3.6 V at a constant current of 0.1 C), shaped, measured the capacity, and other processes to obtain a soft-pack lithium-ion battery (thickness 3.3 mm, width 39 mm, length 96 mm).

[0083] 2.Measurement method (1) Measurement of cycle performance of lithium-ion batteries at 45°C The lithium-ion battery was placed in a 45°C incubator and left to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. After the temperature of the lithium-ion battery had become constant, it was charged at a constant current of 1C until the voltage reached the charge cutoff voltage UV, then charged at a constant voltage of the charge cutoff voltage UV until the current reached 0.05C, and then discharged at a constant current of 1C until the voltage reached 2.8V. This constituted one charge-discharge cycle. The capacity of the initial discharge was taken as 100%. The charge-discharge cycle was repeated until the discharge capacity attenuated to 80%, at which point the measurement was stopped and the number of cycles was recorded, and this was used as an index to evaluate the cycle performance of the lithium-ion battery.

[0084] (2) High-temperature storage measurement of lithium-ion batteries The lithium-ion battery was placed in a 25°C incubator and left to stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. It was charged at a constant current of 1C until it reached the charge cut-off voltage UV, then charged at a constant voltage until the current reached 0.05C, and then discharged at a constant current of 1C to 2.8V, and the discharge capacity was recorded and used as the initial capacity of the lithium-ion battery. It was then charged at a constant current of 0.5C until it reached the charge cut-off voltage UV, and charged at a constant voltage until the current reached 0.05C, and the thickness of the battery was measured and recorded with a micrometer. The lithium-ion battery for measurement was transferred to a 60°C incubator and stored for 90 days, during which the thickness of the battery was measured and recorded once every 3 days. After storing for 90 days, the battery was transferred to a 25°C incubator, left to stand for 60 minutes, and discharged at a constant current of 1C to 2.8V, and the discharge capacity was recorded and used as the remaining capacity of the lithium-ion battery. The battery was charged at a constant current of 1C up to 4.45V, then charged at a constant voltage down to 0.05C, and discharged at a constant current of 1C down to 2.8V. The discharge capacity was recorded and used as the recoverable capacity of the lithium-ion battery. The cell's THK-Thickness, OCV-Open circuit voltage, and IMP-Impedance were measured. The storage thickness expansion rate of the lithium-ion battery was calculated and used as an index to evaluate the amount of high-temperature storage gas generation of the lithium-ion battery. Thickness expansion rate = (thickness after 24 hours storage - initial thickness) / initial thickness x 100%

[0085] (3) Measurement of DC resistance (DCR) (0℃) of lithium-ion battery The lithium-ion battery was placed in a high-temperature / low-temperature box at 0°C and left to stand for 4 hours to allow the lithium-ion battery to reach a constant temperature. It was charged at a constant current of 0.1C until it reached UV, then charged at a constant voltage until the current reached 0.05C, and left to stand for 10 minutes. It was then discharged at a constant current of 0.1C to 3.4V, and the capacity of this step was recorded as the actual discharge capacity D0. It was then left to stand for 5 minutes, charged at a constant current of 0.1C to the charge cut-off voltage UV, and charged at a constant voltage until the current reached 0.05C (the current was calculated corresponding to the D0 capacity). It was left to stand for 10 minutes, and discharged at a constant current of 0.1C for 3 hours (the current was calculated corresponding to the D0 capacity), and the voltage V1 at this time was recorded. It was then discharged at a constant current of 1C for 1 second (10ms sampling, the current was calculated corresponding to the label capacity of the cell), and the voltage V2 at this time was recorded. The DC resistance corresponding to the 70% SOC state of the cell was then calculated. The calculation formula is as follows: 70%SOC DCR=(V2-V1) / 1C

[0086] (4) Lithium-ion battery overcharge test At 25°C, the battery was discharged at 0.5C to 2.8V, charged at a constant current of 3C to 5.7V, and then charged at a constant voltage for 3 hours, and the change in the cell surface temperature (based on the criterion that the cell does not ignite, burn, or explode) was monitored.

[0087] (5) Calendar life of lithium-ion batteries (ITC measurement) The lithium-ion battery was placed in a 45°C incubator and left for 30 minutes to allow the lithium-ion battery to reach a constant temperature. The lithium-ion battery, whose temperature had become constant, was charged at a constant current of 1C until the voltage reached the charge cutoff voltage UV, then charged at a constant voltage of UV until the current reached 0.05C (the initial thickness of the battery was measured and recorded with a micrometer), left at 45°C for 24 hours, and then discharged at a constant current of 1C until the voltage reached 2.8V, which constituted one charge-discharge cycle. The capacity of the initial discharge was taken as 100%. The charge-discharge cycle was repeated, and the measurement was stopped when the discharge capacity had decayed to 80%. Before stopping the measurement, the lithium-ion battery was left at rest for 30 minutes in a 25°C incubator to allow the lithium-ion battery to reach a constant temperature. Once the temperature had stabilized, the lithium-ion battery was charged at a constant current of 1C until the voltage reached UV, and then charged at a constant voltage of UV until the current reached 0.05C (the thickness of the battery after cycling was measured and recorded with a micrometer), and the number of cycles was recorded and used as an index for evaluating the calendar life of the lithium-ion. Thickness expansion rate = (thickness after cycles - initial thickness) / initial thickness * 100%

[0088] (6) Measurement of float charge performance of lithium-ion batteries (CV measurement) The lithium-ion battery was placed in a 25°C incubator and left for 30 minutes to allow the lithium-ion battery to reach a constant temperature. It was charged at a constant current of 1C until the voltage reached UV, then at a constant voltage until the current reached 0.05C, and the thickness of the battery was measured with a micrometer and recorded as the initial thickness. The lithium-ion battery for measurement was transferred to a 45°C incubator and charged at a current of 1C for 60 days. After completion of the charging, the battery was transferred to a 25°C incubator and the thickness of the battery was measured and recorded. The thickness expansion rate during the float charge measurement of the lithium-ion battery was calculated and used as an index to evaluate the float charge performance of the lithium-ion battery. Thickness expansion rate = (thickness after 60 days of float charging - initial thickness) / initial thickness x 100%

[0089] 3. Measurement results Table 1 shows the effects of the nickel content in the positive electrode active material, the charge cutoff voltage, and the fluoroethylene carbonate (FEC) content in the electrolyte on the resistance, cycle capacity retention, and high temperature storage expansion rate of the lithium ion battery. The positive electrode active material used in each of the examples and comparative examples in Table 1 is represented by the general formula LiNi x Co y Mn z Lithium nickel manganese cobalt ternary material represented by LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 The organic solvent components in the electrolyte used in each of the Examples and Comparative Examples in Table 1 were a mixture of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of EC:PC:EMC:DEC = 20:20:20:40, and contained fluoroethylene carbonate as an additive.

[0090] [Table 1]

[0091] As can be seen from the results, limiting the nickel content in the positive electrode active material, the charge cutoff voltage, and the fluoroethylene carbonate (FEC) content in the electrolyte have a very important effect on improving the resistance, high-temperature storage expansion rate, and cycle capacity retention rate under high-voltage operating conditions of lithium-ion batteries. Specifically, as shown in Table 1, the charge cutoff voltage UV, the molar content x of nickel in the positive electrode active material, and the mass content a% of fluoroethylene carbonate in the electrolyte are

number

[0092] Table 2 shows the nickel content in the positive electrode active material, the charge cutoff voltage, and the fluoroethylene carbonate (FEC) content in the electrolyte, as well as the effect of adding a sulfur-oxygen double bond compound to the electrolyte on the resistance, cycle capacity retention rate, high temperature storage expansion rate, and overcharge performance of the lithium ion battery. The positive electrode active material used in each of the examples and comparative examples in Table 2 is represented by the general formula LiNi x Co y Mn z Lithium nickel manganese cobalt ternary material represented by LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05The organic solvent components in the electrolyte used in each of the Examples and Comparative Examples in Table 2 were ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) mixed in a mass ratio of EC:PC:EMC:DEC=20:20:20:40, and contained fluoroethylene carbonate and a sulfur-oxygen double bond compound as an additive. The specific types and weight percentages of the sulfur-oxygen double bond compounds were as shown in Table 2.

[0093] [Table 2]

[0094] As can be seen from the results in Table 2, the electrolyte can further include a sulfur-oxygen double bond compound, which can form a stable solid electrolyte interfacial film on the surface region of the positive electrode active material to improve the structural stability of the positive electrode active material, and can improve the phase change and surface resistance of the positive electrode active material. The charge cutoff voltage UV, the molar content x of nickel in the positive electrode active material, and the mass content a% of fluoroethylene carbonate in the electrolyte can be calculated as follows:

number

number

[0095] Table 3 shows the effects of the nickel content in the positive electrode active material, the charge cutoff voltage, the fluoroethylene carbonate (FEC) content in the electrolyte, and the type of organic solvent in the electrolyte on the resistance, cycle capacity retention rate, high temperature storage expansion rate, and overcharge performance of the lithium ion battery. The positive electrode active material used in each of the examples and comparative examples in Table 3 is represented by the general formula LiNi x Co y Mn z Lithium nickel manganese cobalt ternary material represented by O2, and the chemical formula is LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 The type and weight percentage of the organic solvent in the electrolyte used in each of the Examples and Comparative Examples in Table 3 are shown in Table 3. The electrolyte contained fluoroethylene carbonate as an additive.

[0096] [Table 3]

[0097] As can be seen from the results in Table 3, the organic solvent in the electrolyte can further adjust the type of linear carbonate to improve the structural stability of the positive electrode active material, and when the linear carbonate is at least one selected from diethyl carbonate and ethyl methyl carbonate, it can improve the side reaction and surface resistance at the interface between the positive electrode active material and the electrolyte. The charge cutoff voltage UV, the molar content x of nickel in the positive electrode active material, and the mass content a% of fluoroethylene carbonate in the electrolyte are:

number

number

[0098] Table 4 shows the nickel content in the positive electrode active material, the charge cutoff voltage, and the fluoroethylene carbonate (FEC) content in the electrolyte, as well as the effect of adding lithium difluorophosphate to the electrolyte on the resistance, cycle capacity retention rate, high temperature storage expansion rate, and overcharge performance of the lithium ion battery. The positive electrode active material used in each of the examples and comparative examples in Table 4 is represented by the general formula LiNi x Co y Mn z Lithium nickel manganese cobalt ternary material represented by O2, and the chemical formula is LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.8 C0 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 The organic solvent components in the electrolyte used in each of the Examples and Comparative Examples in Table 4 were a mixture of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of EC:PC:EMC:DEC = 20:20:20:40, and the electrolyte contained fluoroethylene carbonate and lithium difluorophosphate as additives.

[0099] [Table 4]

[0100] As can be seen from the results in Table 4, adding lithium difluorophosphate to the electrolyte can further form a thin and uniform low-resistance protective layer at the interface between the positive electrode active material layer and the negative electrode active material layer, and the electrochemical window of lithium difluorophosphate is wide, which can effectively suppress side reactions at the interface between the electrolyte and the electrode. The charge cutoff voltage UV, the molar content x of nickel in the positive electrode active material, and the mass content a% of fluoroethylene carbonate in the electrolyte are

number

number

[0101] Table 5 shows the nickel content in the positive electrode active material, the charge cutoff voltage, and the fluoroethylene carbonate (FEC) content in the electrolyte, as well as the effect of adding a polynitrile compound to the electrolyte on the resistance, cycle capacity retention rate, high temperature storage expansion rate, and overcharge performance of the lithium ion battery. The positive electrode active material used in each of the examples and comparative examples in Table 5 is represented by the general formula LiNi x Co y Mn z Lithium nickel manganese cobalt ternary material represented by O2, and the chemical formula is LiNi 0.33 Co 0.33 Mn 0.33 O2, LiNi 0.5 Co 0.2 Mn0.3 O2, LiNi 0.6 Co 0.1 Mn 0.3 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.9 Co 0.05 Mn 0.05 O2. The organic solvent components in the electrolyte used in each of the examples and comparative examples in Table 5 were ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) mixed in a mass ratio of EC:PC:EMC:DEC = 20:20:20:40, and the electrolyte contained fluoroethylene carbonate and a polynitrile compound as additives. See Table 5 for the type and weight percent of the polynitrile compound.

[0102] As can be seen from the results in Table 5, the addition of a polynitrile compound to the electrolyte can further enhance the protection of the interface between the positive electrode active material layer and the negative electrode active material layer of the nickel-containing positive electrode active material system. The charge cutoff voltage UV, the molar content x of nickel in the positive electrode active material, and the mass content a% of fluoroethylene carbonate in the electrolyte are:

number

[0103] [Table 5]

[0104] Throughout the specification, references to "embodiments," "some embodiments," "one embodiment," "another embodiment," "an example," "particular example," or "some examples" mean that at least one embodiment or example of the invention includes a particular feature, structure, material, or feature described in that embodiment or example. Thus, references to, for example, "in some embodiments," "in an embodiment," "in one embodiment," "in other embodiments," "in one example," "in a particular example," or "an example" in various parts throughout the specification do not necessarily refer to the same embodiment or example of the invention. Furthermore, particular features, structures, materials, or features herein may be combined in any suitable manner in one or more embodiments or examples.

[0105] Although illustrative embodiments have been disclosed and described, those skilled in the art should understand that the above-described embodiments should not be construed as limiting the present invention, and that the embodiments can be modified, substituted, and altered without departing from the spirit, principle, and scope of the present invention.

Claims

1. 1. An electrochemical device comprising: A positive electrode and an electrolyte are included. The positive electrode includes a positive electrode active material layer, The positive electrode active material layer contains a positive electrode active material, The positive electrode active material includes lithium nickel oxide, The electrolyte contains fluoroethylene carbonate, The mass content of the fluoroethylene carbonate is a % based on the total mass of the electrolyte, and the charge cutoff voltage U V of the electrochemical device, the molar content x of nickel in the lithium nickel oxide, and the mass content a % of the fluoroethylene carbonate in the electrolyte are [0010] Electrochemical device.

2. The electrochemical device according to claim 1 , wherein x satisfies 0.3<x≦1.

3. The lithium nickel oxide has the general formula LiNi x M1 y M2 z O 2 Or n [Li 2 MnO 3 ]・(1-n)[LiNi x M1 y M2 z O 2 wherein M1 and M2 comprise one or more of Co, Mn, Al, Mg, Ti, and Zr, and 0.3≦x≦1, 0≦y≦0.7, 0≦z≦0.7, and 0≦n<1.

4. 2. The electrochemical device of claim 1, wherein the charge cut-off voltage U of the electrochemical device is between 4.2V and 5.5V.

5. 2. The electrochemical device according to claim 1, wherein the mass content a % of the fluoroethylene carbonate in the electrolyte is 0.05% to 5.3%.

6. The electrochemical device of claim 1 , wherein the electrolyte further comprises a sulfur-oxygen double bond compound.

7. 7. The electrochemical device of claim 6, wherein the sulfur-oxygen double bond compound comprises one or more of 1,3-propane sultone (PS), 2,4-butane sultone, 1,4-butane sultone, ethylene sulfate (DTD), propene-1,3-sultone (PES), methylenemethane disulfonate (MMDS), vinyl sulfone (DVS), 1,2,6-oxadithiane, 2,2,6,6-tetraoxide (CAS: 4720-58-5), 4-methylethylene sulfate (PCS), 3-sulfolene, dihydro-1,3,2-dioxathiolo[1,3,2]dioxathiole-2,2,5,5-tetraoxide (CAS: 496-45-7), and pentaerythritol bicyclosulfate compounds.

8. Based on the total mass of the electrolyte, the mass content of the sulfur-oxygen double bond compound is b%, and the mass content of the sulfur-oxygen double bond compound is b% and the mass content of the fluoroethylene carbonate is a%. [0025] The electrochemical device according to claim 6 ,

9. 7. The electrochemical device according to claim 6, wherein the mass content b % of the sulfur-oxygen double bond compound is 0.1% to 5% based on the total mass of the electrolyte.

10. The electrolyte further comprises an organic solvent and a lithium salt; The organic solvent comprises a linear carbonate, 2. The electrochemical device according to claim 1, wherein the linear carbonate is at least one selected from the group consisting of dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.

11. Based on the total mass of the organic solvent, the mass content of the linear carbonate is 70% or less, and / or 11. The electrochemical device according to claim 10, wherein the mass content of the linear carbonate is 60% or less, based on the total mass of the electrolyte.

12. Based on the total mass of the electrolyte, the mass content of the linear carbonate having a molecular molar mass of more than 100 in the linear carbonate is c%, and the mass content c% of the linear carbonate having a molecular molar mass of more than 100 and the mass content a% of the fluoroethylene carbonate are [0030] The electrochemical device according to claim 10 ,

13. The electrochemical device according to claim 10, wherein the mass content c% of the linear carbonate is 20% to 60% based on the total mass of the electrolyte.

14. 2. The electrochemical device of claim 1, wherein the electrolyte further comprises an additive, lithium difluorophosphate.

15. The mass content of the additive lithium difluorophosphate is d% based on the total mass of the electrolyte solution, and the mass content d% of the additive lithium difluorophosphate and the molar content x of nickel in the lithium nickel oxide are expressed as follows: [0045] The electrochemical device according to claim 14 ,

16. 15. The electrochemical device according to claim 14, wherein the mass content d% of the additive lithium difluorophosphate is 0.01% to 1% based on the total mass of the electrolyte solution.

17. The electrolyte further comprises a polynitrile compound, 2. The electrochemical device of claim 1, wherein the polynitrile compound comprises one or more of a dinitrile compound, a trinitrile compound, and a tetranitrile compound.

18. the dinitrile compound comprises one or more of succinonitrile, adiponitrile, 1,2-bis(cyanoethoxy)ethane, and 1,4-dicyano-2-butene; The trinitrile compound includes one or more of 1,3,6-hexanetricarbonitrile and 1,2,3-tris(2-cyanoethoxy)propane; 18. The electrochemical device of claim 17, wherein the tetranitrile compound comprises one or more of 1,1,3,3-propanetetracarbonitrile, 1,1,2,2-ethanetetracarbonitrile, 4-(2-cyanoethyl)-4-cyanopimelonitrile, and pentane-1,3,3,5-tetracarbonitrile.

19. The electrochemical device according to claim 17, wherein the mass content of the polynitrile compound is 0.1% to 5% based on the total mass of the electrolyte.

20. An electronic device comprising an electrochemical device according to any one of claims 1 to 19.

Citation Information

Patent Citations

  • Lithium ion finished battery and preparation method thereof

    CN111640984A

  • Nonaqueous electrolyte and lithium secondary battery using the same

    JP2012079711A

  • Lithium secondary battery

    JP2013098027A

  • Secondary battery and device comprising the secondary battery

    WO2021127997A1